PENGARUH PENDAPATAN SENDIRI DAN DANA PERIMBANGAN TERHADAP BELANJA MODAL DENGAN DANA OTONOMI KHUSUS SEBAGAI PEMODERASI PADA KAB/KOTA DI PROVINSI ACEH - nufus, hayatun; Asmara, Jhon Andra (Accounting Departement Economics and Business Faculty Syiah Kuala University, 2017)
The objective of the research was to find out the influence of Local Own Revenue and Balancing Fund on Capital Expenditure simultaneously and partially in Province/City Government in Aceh, and the role of Special Autonomy Fund in moderating the relationship of Local Own Revenue and Balancing Fund with Capital Expenditure. The research used causal design. The population was 23 provinces/cities in Aceh, and whole observed. The period of observation was since 2014 until 2016, so there were 69 analysis units all together. The data were processed by using multiple linear regression tests with an SPSS software program. The result of the research showed that Local Own Revenue and Balancing Fund both simultaneosly and partially influenced Capital Expenditure. Special Autonomy Fund could moderate the relationship of Local Own Revenue and Balancing Fund with Capital Expenditure.